2008
DOI: 10.1007/s10529-008-9696-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tryptophan tags on the purification of cutinase, secreted by a recombinant Saccharomyces cerevisiae, using cationic expanded bed adsorption and hydrophobic interaction chromatography

Abstract: During cationic bed adsorption (EBA), with cutinase with varying length tryptophan tags (WP)(2)and (WP)(4), 33% and 10% of adsorption capacity and 80% and 32% eluted specific activity were observed in relation to wild type (wt)-cutinase in the conventional process. Therefore, as the hydrophobicity of the protein increases, it is important to integrate the EBA step with a hydrophobic interaction chromatography (HIC) process. As the length of the hydrophobic tag-(WP) increases from n = 2 to n = 4, the purificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A likely application of these hydrophobic supports, still to be reported is the one-step immobilization-purification of chimeric proteins bearing hydrophobic tags, some papers show how using hydrophobic supports, these tagged enzymes may be selectively immobilized [111][112][113]. These proteins should have a large affinity for these hydrophobic supports.…”
Section: Discussionmentioning
confidence: 99%
“…A likely application of these hydrophobic supports, still to be reported is the one-step immobilization-purification of chimeric proteins bearing hydrophobic tags, some papers show how using hydrophobic supports, these tagged enzymes may be selectively immobilized [111][112][113]. These proteins should have a large affinity for these hydrophobic supports.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of hydrophobic tags for recombinant protein purification include tags based on tryptophan and tyrosine, exploited for aqueous two phase separation (ATPS) , and tags based on repetitions of the dipeptide tryptophan-proline (WP) n (Lienqueo et al, 2008). It has been reported that as the length of the tag increases, a negative effect on cellular growth, stability of the plasmids, secretion efficiency of the target protein and a decrease of recovery yield on purification stage are observed (Lienqueo et al, 2008).…”
Section: Hydrophobic Tagsmentioning
confidence: 99%
“…Examples of hydrophobic tags for recombinant protein purification include tags based on tryptophan and tyrosine, exploited for aqueous two phase separation (ATPS) , and tags based on repetitions of the dipeptide tryptophan-proline (WP) n (Lienqueo et al, 2008). It has been reported that as the length of the tag increases, a negative effect on cellular growth, stability of the plasmids, secretion efficiency of the target protein and a decrease of recovery yield on purification stage are observed (Lienqueo et al, 2008). According to Collén et al, during protein expression, fully exposed hydrophobic tags can reduce target protein solubility, compromising the secretion pathway and leading to the formation of insoluble protein aggregates (Collén et al, 2001) and the chance that the target protein will be membraneassociated increases .…”
Section: Hydrophobic Tagsmentioning
confidence: 99%